Financial Literacy, Performance, And Welfare Of Msmes In Gianyar Regency - Gde Bagus Brahma Putra; Putu Yenny Astiti; Ni Putu Lisa Ernawatiningsih; Made Ika Prastyadewi (Universitas Udayana, 2025)
This study aims to 1). Analyzing the effect of financial literacy on the performance of MSMEs, 2).Analyzing the effect of financial literacy on the welfare of MSME actors, and 3). Analyzing theeffect of MSME performance on the welfare of MSME actors. The research was conducted inGianyar Regency and focused on 110 MSME actors. The data sources used are primary data frombamboo weaving crafters and secondary data from various relevant agencies. The analysis resultsshow that financial literacy affects the performance and welfare of MSME actors, and performancealso affects their welfare. The results of this analysis also show that good financial literacy will beable to improve the performance of MSMEs, especially in facing digital developments and variousglobal challenges.